Prioritization of factors affecting agency value for an airline company using fuzzy cognitive mapping method - Özer, Muhammed Fatih (Graduate School, 2023)
The civil aviation sector has witnessed significant growth in the 21st century, with remarkable advancements in both the operational capabilities of companies and the increasing demand from passengers. Despite the rapid growth in capacity and demand within the sector, companies have consistently faced the challenge of operating with low profit margins. Moreover, the seat inventory of airlines for each flight is limited and perishable. Thus, airlines must carefully plan and optimize their flight ticket pricing strategies to maximize their revenue. Revenue management is an area where it is aimed to maximize revenue by selling the right product to the right customer with the right price at the right time. In airline revenue management, generally, discounted fares are offered for agencies requesting group reservations compared to individual fares. This is because group bookings are seen as a more stable source of revenue for airlines. Especially in the Covid-19 period, the agencies whose business was seriously damaged requested the lowest prices they can get, to be able to find passengers and make a profit. The airlines were also in a financial crisis and must have balanced the prices to make a profit while attracting the agencies. From this perspective, the need for customer segmentation and defining the value of agencies for airlines arised once again. The purpose of this study is to define the parameters the agency creates while making business with airlines, and determine the prioritization of these parameters by identifying their importance that creates the value of an agency for an airline by using Fuzzy Cognitive Mapping (FCM). While businesses can leverage their years of experience and knowledge to facilitate this process and draw inferences from past actions, there is a constant pursuit for efficient and targeted methods that enable more accurate decision-making and cost-effective problem-solving. The FCM method emerges as a highly effective approach, as it not only enables the creation of meaningful relationship maps based on research outcomes but also assists businesses in making cost-effective decisions. Consequently, the decision to employ the FCM method was made to address the problem at hand in this study. This study examines and prioritizes the variables that might affect the value of agencies to an airline through the weight of these variables in order to create insights into the pricing strategies of airlines to travel agencies. The determined parameters are assessed by airline pricing specialists who possess extensive experience and have strong knowledge in the sector in order to establish the relationship between these parameters and analyze them using the FCM method. Through the implementation of FCM, 3 most critical parameters of agencies for airlines out of 10 were found and ordered by their importance as follows, "Annual reservation volume", "the agency's sensitivity to the fare offers / being very negotiative" and "the ratio of the airline to the total business volume of the agency".
Bir havayolu şirketi için acente değerini etkileyen faktörlerin bulanık bilişsel haritalama yöntemi ile önceliklendirilmesi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: airline company; fuzzy cognitive mapping method; civil aviation